Diagnostic Accuracy of FNAC – Fine Needle Aspiration Cytology in Thyroid Lesions while taking Histopathology as Gold Standard (Journal of Fatima Jinnah Medical University, 2018)
Objective: The objective of this study was to prove the efficacy of thyroid FNAC in cases benign non-neoplastic lesions and malignant lesions.Study Design: Cross Sectional SurveySetting: Department of Pathology (Histopathology Section), Fatima Jinnah Medical College, LahoreSubject and Methods: Fine Needle Aspiration Cytology (FNAC) was used as a diagnostic procedure in the Department of Pathology (Histopathology Section), Fatima Jinnah Medical College, Lahore, for the past fifteen years. We have collected the data for past 4 years, (from 2003 to 2007), of FNAC and correlated with Histopathology. We included 130 cases, in which FNAC was done followed by surgery.Results: In this study diagnostic accuracy of FNAC in cases of benign lesions was 86.95%, and it was 13.05% in cases of neoplastic lesions.Conclusion: According to this study the efficacy of FNAC is high in cases of benign and malignant lesions except for follicular adenoma/carcinoma whose diagnosis is based on biopsy rather than cytology.
Keywords: Fine Needle Aspiration Cytology, Histopathology Correlation.